2019
DOI: 10.1093/pcp/pcz137
|View full text |Cite
|
Sign up to set email alerts
|

Class I TCP Transcription Factors Target the Gibberellin Biosynthesis GeneGA20ox1and the Growth-Promoting GenesHBI1andPRE6during Thermomorphogenic Growth inArabidopsis

Abstract: Plants respond to a rise in ambient temperature by increasing the growth of petioles and hypocotyls. In this work, we show that Arabidopsis thaliana class I TEOSINTE BRANCHED 1, CYCLOIDEA, PCF (TCP) transcription factors TCP14 and TCP15 are required for optimal petiole and hypocotyl elongation under high ambient temperature. These TCPs influence the levels of the DELLA protein RGA and the expression of growth-related genes, which are induced in response to an increase in temperature. However, the class I TCPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 54 publications
0
43
1
Order By: Relevance
“…GA20ox plays a key role in the GA biosynthesis pathway and affects bioactive GA content (Yamaguchi, 2008). In A. thaliana, the over-expression of GA20ox enhances hypocotyl elongation (Huang et al, 1998;Coles et al, 1999;Ferrero et al, 2019), and the expression of GA20ox (GA20ox1) is upregulated by high temperatures in hypocotyls (Stavang et al, 2009). Thus, it is suggested that SlGA20ox1 plays a key role in regulating stem elongation in tomato seedlings in response to different DIF conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GA20ox plays a key role in the GA biosynthesis pathway and affects bioactive GA content (Yamaguchi, 2008). In A. thaliana, the over-expression of GA20ox enhances hypocotyl elongation (Huang et al, 1998;Coles et al, 1999;Ferrero et al, 2019), and the expression of GA20ox (GA20ox1) is upregulated by high temperatures in hypocotyls (Stavang et al, 2009). Thus, it is suggested that SlGA20ox1 plays a key role in regulating stem elongation in tomato seedlings in response to different DIF conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that phytohormones are involved in regulating plant growth in response to temperature. Gibberellin (GA) is known to play a key role in stem elongation (Davière and Achard, 2013;Binenbaum et al, 2018;Ferrero et al, 2019). Indole-3-acetic acid (IAA), an auxin, also plays an important role in cell elongation in the hypocotyl, the epicotyl, and other organs (Leyser, 2018;Zhao, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies on the functional information of Class I TCP members, which are involved in plant development, growth, and proliferation. For example, AtTCP14 and AtTCP15 regulate embryonic growth via the gibberellin signaling pathway during seed germination (Resentini et al, 2015), and AtTCP15 directly acts on GA20ox1, HBI1, and PRE6 to promote petiole growth and hypocotyl elongation (Ferrero et al, 2019). In Arabidopsis, a tcp23-knockout line has an early-flowering phenotype, while overexpression lines exhibit the reverse phenotype, which indicates that AtTCP23 participates in the regulation of flowering (Balsemao-Pires et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhou et al (2018) reported overexpression of TCP17 leads to a long hypocotyl phenotype in Arabidopsis. TCP14 and TCP15 are required for optimal elongation and for the appropriate gene expression responses to a group of auxin inducible genes and the GA biosynthetic gene GA20ox1 in hypocotyls of Arabidopsis (Ferrero et al 2019;Ferrero et al 2021). Based on the transcriptome data, combined the knowledge from scienti c literature, we speculate that the hypocotyl elongation in elh1 is mainly due to the interaction and cooperative regulation of phys, GA/Auxin, cell cell-elongation-related genes and these differential TFs.…”
Section: Discussionmentioning
confidence: 99%